The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1051/0004-6361/201117154
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the Cepheid period-luminosity relation from the infrared surface brightness technique

Abstract: Context. The extragalactic distance scale builds directly on the Cepheid period-luminosity (PL) relation as delineated by the sample of Cepheids in the Large Magellanic Cloud (LMC). However, the LMC is a dwarf irregular galaxy, quite different from the massive spiral galaxies used for calibrating the extragalactic distance scale. Recent investigations suggest that not only the zero-point but also the slope of the Milky Way PL relation differ significantly from that of the LMC, casting doubts on the universalit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
111
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 45 publications
22
111
1
Order By: Relevance
“…Gieren et al (2005) required the period-projection factor relation to be p = −0.15 log P+1.58 to measure a distance to the LMC that is independent of Cepheid pulsation period. Storm et al (2011b) found similar results for LMC Cepheids, also using the infrared surface brightness technique, for different observations. Furthermore, Storm et al (2011a) used observations of Galactic Cepheids with known HST parallaxes to verify the steeper period dependence of the projection factor; we refer to this type of analysis as the LMC-HST Pp relation and p-factor.…”
Section: Introductionsupporting
confidence: 74%
“…Gieren et al (2005) required the period-projection factor relation to be p = −0.15 log P+1.58 to measure a distance to the LMC that is independent of Cepheid pulsation period. Storm et al (2011b) found similar results for LMC Cepheids, also using the infrared surface brightness technique, for different observations. Furthermore, Storm et al (2011a) used observations of Galactic Cepheids with known HST parallaxes to verify the steeper period dependence of the projection factor; we refer to this type of analysis as the LMC-HST Pp relation and p-factor.…”
Section: Introductionsupporting
confidence: 74%
“…We choose the work by Ripepi et al (2012b) as reference for CCs because: i) these Authors adopted a procedure similar to the one adopted in this work; ii) their results are in excellent agreement with the most recent and accurate literature findings (see e.g. Storm et al 2011b;Laney, Joner, & Pietrzyński 2012;Walker 2012;Pietrzyński et al 2013;de Grijs, Wicker, & Bono 2014, and references therein) An analysis of Table 6 reveals that: i) the inclusion of the two stars with BW-based distances does not change significantly the ZP s and ii) there is a difference of at least ∼0.1 mag between the ZP s calibrated on the basis of CCs and of Galactic T2CEPs (see Sect. 5).…”
Section: Absolute Calibration Of P L P Lc and P W Relationsmentioning
confidence: 76%
“…We computed the PSR B0540−69 luminosity by using as a reference the most recent value of the LMC distance (48.97 ± 0.9 kpc), obtained from re-calibrating the Cepheids period-luminosity relation (Storm et al 2011). At the assumed distance, the measured extinction-corrected K-band flux of PSR B0540−69 corresponds to a luminosity L K ∼ 2.8 × 10 33 erg s −1 .…”
Section: The Pulsar Infrared Luminositymentioning
confidence: 99%